The effectiveness of psychosocial and vocational training for mentally challenged in a day care centre - Hazarika, Mythili (J Rural Community Psychiatr, 2014)
BACKGROUND: A growing number of mentally challenged individual are being excluded mainly from the educational process because of a presumed inability to learn. AIM: The study is aimed at identifying the efficacy of psychosocial and vocational training for mentally challenged in a day care centre. METHODS: The sample for the study consisted of 30 clinically diagnosed mentally challenged children (N=30, boy=18, girl=12), who are enrolled in Ashadeep day care centre. Methods employed were a semi demographic questionnaire and Vineland Social Maturity Scale to assess the improvement of the child across the various subscales in the pre post test sessions. Correlation coefficient and t-test was used to compare the profile of the children across both the sessions. RESULTS: Age of onset of therapy and the duration does not have significant effect on the outcome, but ‘higher the IQ’ more positive outcome can be seen. The subscales do not correlate when it comes to affecting each other. Girls showed much poor outcomes than boys in the self0help general subscale. CONCLUSIONS: The study ascertained the fact that education and training of the mentally subnormal child is also possible, and psychosocial and vocational training lead to improving the social competence of the child.